Preliminary Study on Physicochemical and Biological Properties of Chitosan Extracted from Mud Crab (Scylla olivacea) Shells - Norhaliza, Ahmad; Awang Ahmad Sallehin, Awang Husaini; Sumiyyah, Sabar; Wan Roslina, Wan Yusof (Institut Kimia Malaysia, 2024)
Chitosan, a non-toxic and biodegradable biopolymer, has been immensely exploited due to its inherent features, such as its ability to inhibit bacterial growth and free radical scavenging. This biopolymer can be extracted from crustaceans, molluscs, insects, or fungi chitin. Interestingly, different sources of this biopolymer affect the physicochemical and biological activities. Thus, this study aims to characterise, compare the physicochemical and biological properties of extracted chitosan (E.ch) from mud crabs, Scylla olivacea (S. olivacea), and commercial chitosan (C.ch). The E.ch was extracted via the chemical method, and their physicochemical and biological properties, such as degree of deacetylation (DD), viscosity, antibacterial, antifungal, as well as antioxidant activity, were characterised. The results revealed that E.ch with high DD and low viscosity showed better antibacterial activity against Pseudomonas aeruginosa (P. aeruginosa), better antifungal activity against Aspergillus flavus (A. flavus) and high antioxidant activity compared to C.ch. The higher DD of E.ch contributed to better antibacterial, antifungal, and antioxidant activity. In conclusion, the findings of this study on the physicochemical and biological properties of E.ch from mud crabs could be utilised in various fields such as biomedical, pharmaceutical, and agriculture applications.